2018
DOI: 10.1002/anie.201809889
|View full text |Cite
|
Sign up to set email alerts
|

Nickel as a Lewis Base in a T‐Shaped Nickel(0) Germylene Complex Incorporating a Flexible Bis(NHC) Ligand

Abstract: Flexible, chelating bis(NHC) ligand 2, able to accommodate both cis-and trans-coordination modes, was used to synthesize (2)Ni(η 2-cod), 3. In reaction with GeCl2, this produced (2)NiGeCl2, 4, featuring a T-shaped Ni(0) and a pyramidal Ge center. Complex 4 could also be prepared from [(2)GeCl]Cl, 5, and Ni(cod)2, in a reaction that formally involved Ni-Ge transmetalation, followed by coordination of the extruded GeCl2 moiety to Ni. A computational analysis showed that 4 possesses considerable multiconfiguratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 81 publications
4
17
0
Order By: Relevance
“…After the isonitriles there are two families of solvents with some ever‐coordinated members, the N‐heterocycles and the thioethers, even if other members of those two families cover a wide range of coordination abilities, with a TM eventually reaching values close to 0.0 (i.e., 50 % of coordinated structures). Among the N‐heterocycles, a remarkable case is that of pyridine, which is commonly bound to transition metals through the N atom, but can alternatively be π‐coordinated in a η 2 mode, in a triply bridging η 2 , η 2 , η 2 mode or fully η 6 coordinated . More striking is the fact that pyridinium cations, disregarded for the study of the coordinating ability of pyridine, can also be found in π‐coordinated modes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the isonitriles there are two families of solvents with some ever‐coordinated members, the N‐heterocycles and the thioethers, even if other members of those two families cover a wide range of coordination abilities, with a TM eventually reaching values close to 0.0 (i.e., 50 % of coordinated structures). Among the N‐heterocycles, a remarkable case is that of pyridine, which is commonly bound to transition metals through the N atom, but can alternatively be π‐coordinated in a η 2 mode, in a triply bridging η 2 , η 2 , η 2 mode or fully η 6 coordinated . More striking is the fact that pyridinium cations, disregarded for the study of the coordinating ability of pyridine, can also be found in π‐coordinated modes .…”
Section: Resultsmentioning
confidence: 99%
“…[128][129][130] After the isonitriles there are two families of solvents with some ever-coordinated members, the N-heterocycles andt he thioethers, even if other members of those two families cover aw ide range of coordination abilities, with a TM eventually reachingv alues close to 0.0 (i.e.,5 0% of coordinated structures). Among the N-heterocycles, ar emarkable case is that of pyridine, which is commonly boundt ot ransitionm etals through the Na tom, but can alternatively be p-coordinated in a h 2 mode, [131,132] in at riply bridging h 2 , h 2 , h 2 mode [133] or fully Table 5. Coordinating ability of gases towards transition metals:c oordinating ability index a TM ,p ercentage of structures in which the anion is found coordinatedo rs emi-coordinated to at ransition metal, and number of structures analysed.D ata for some non gaseous neutral ligands also given for comparison.…”
Section: Gasesmentioning
confidence: 99%
“…The Ge center of germylene complexes generally takes a trigonal‐planar geometry, but pyramidalized base‐free germylene complexes have recently been reported for the first time by Braunschweig et al., that is, dichlorogermylene platinum complexes L(Cy 3 P)Pt=GeCl 2 (L=PCy 3 , IMes) (IMes=1,3‐bis(2,4,6‐trimethylphenyl)imidazol‐2‐ylidene) . This type of pyramidalized germylene ligand can also be seen in a very recently reported nickel germylene complex, but is still very rare. Moreover, reactivity of the pyramidalized germylene centers have never been reported.…”
Section: Methodsmentioning
confidence: 83%
“…Hydrogen atoms are omitted for clarity except for the Ha toms on the Ba tom. Selectedb ond lengths ()and angles (8): NiÀGe 2.3370(8), NiÀP1 2.2117(15), NiÀP2 2.2325(16), NiÀC1 1.986(5), GeÀC2 1.981(5),Ge ÀC8 1.972(6), GeÀB2 .109(7),Ge-Ni-C1151.81(16), P1-Ni-P2 142.90(6), Ni-Ge-C2 108.90(16), Ni-Ge-C8 108.27(15), Ni-Ge-B 108.27(15), C2-Ge-C8 109.0(2).…”
mentioning
confidence: 99%
“…Solution 1 H NMR analysis of 2 revealed a broad, complex spectrum denoting C 1 symmetry, reflected in the 13 C NMR spectrum by the presence of two resonances for the coordinated carbene carbons (200.4 and 208.4 ppm). Reduced conformational fluxionality in complexes containing bis(NHC)Ni fragments was shown to lead to broad, poorly resolved resonances in the solution NMR spectra, as well as lowering of the expected time‐averaged symmetry [27] . An X‐ray diffraction experiment on 2 confirmed chelation of the ligand to Ni in a bent geometry (C1‐Ni1‐C8 107.9(1)°) (Figure S28) and the η 2 ‐coordination of 1,5‐cyclooctadiene.…”
Section: Figurementioning
confidence: 99%